2022
DOI: 10.3390/cancers14225720
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Opioids on Survival in Patients with Cancer

Abstract: Opioids are commonly used for pain management in patients with cancer. They have a range of unwanted effects, including some that potentially influence cancer growth. This article reviews the data assessing the effects of opioids on survival in patients with cancer. Many studies assessing this show an association between opioids and decreased survival. This effect is present even at very low doses of opioids. These studies do not assess causality, so it is not known if it is a direct effect of opioids on survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Opioids may have fewer side effects when administered under analgesic ladder therapy guidance; however, opioid therapy may entail gastrointestinal symptoms such as nausea, vomiting, and constipation, as well as central effects ranging from sedation to unconsciousness and respiratory depression. These risks are particularly notable when considering the overall disease course of cancer and the similar adverse effects associated with chemotherapy and radiotherapy [15]. Adjuvant agents such as pregabalin, gabapentin, and duloxetine can be used to treat patients with cancer-related neuropathic pain or in cases of inadequate current treatment [16].…”
Section: Discussionmentioning
confidence: 99%
“…Opioids may have fewer side effects when administered under analgesic ladder therapy guidance; however, opioid therapy may entail gastrointestinal symptoms such as nausea, vomiting, and constipation, as well as central effects ranging from sedation to unconsciousness and respiratory depression. These risks are particularly notable when considering the overall disease course of cancer and the similar adverse effects associated with chemotherapy and radiotherapy [15]. Adjuvant agents such as pregabalin, gabapentin, and duloxetine can be used to treat patients with cancer-related neuropathic pain or in cases of inadequate current treatment [16].…”
Section: Discussionmentioning
confidence: 99%
“…MOR expression is associated with opioid use. Intraoperative opioid use increases MOR expression in cancer tissues ( 36 , 37 ), and also exacerbates shorter survival ( 38 ). Contrarily, sufentanil consumption was higher in the MOR high expression group ( 21 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that even a limited dose of opioids may lead to addiction; long-term opioids use increases the mortality of patients [ 10 , 11 ]. Opioids may lead to tumor growth, angiogenesis and distant spread through transactivation of vascular endothelial growth factor (VEGF) receptors and increased expression of opioid receptors, which is closely related to the prognosis of cancer patients [ 12 ]. High doses of opioids carry a risk of long-term dependence, with 10 percent of patients continuing to use opioids for up to 90 days after undergoing a series of major and minor surgeries [ 2 ].…”
Section: Introductionmentioning
confidence: 99%